Methicillin-resistant Staphylococcus aureus and Acinetobacter baumannii on computer interface surfaces of hospital wards and association with clinical isolates - Ma Ling (BMC Infectious Diseases, 2009)
Abstract Background Computer keyboards and mice are potential reservoirs of nosocomial pathogens, but routine disinfection for non-water-proof computer devices is a problem. With better hand hygiene compliance of health-care workers (HCWs), the impact of these potential sources of contamination on clinical infection needs to be clarified. Methods This study was conducted in a 1600-bed medical center of southern Taiwan with 47 wards and 282 computers. With education and monitoring program of hand hygiene for HCWs, the average compliance rate was 74% before our surveillance. We investigated the association of methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa and Acinetobacter baumannii, three leading hospital-acquired pathogens, from ward computer keyboards, mice and from clinical isolates in non-outbreak period by pulsed field gel electrophoresis and antibiogram. Results Our results revealed a 17.4% (49/282) contamination rate of these computer devices by S. aureus, Acinetobacter spp. or Pseudomonas spp. The contamination rates of MRSA and A. baumannii in the ward computers were 1.1% and 4.3%, respectively. No P. aeruginosa was isolated. All isolates from computers and clinical specimens at the same ward showed different pulsotypes. However, A. baumannii isolates on two ward computers had the same pulsotype. Conclusion With good hand hygiene compliance, we found relatively low contamination rates of MRSA, P. aeruginosa and A. baumannii on ward computer interface, and without further contribution to nosocomial infection. Our results suggested no necessity of routine culture surveillance in non-outbreak situation.